ALGORITHM OF ANALYSIS the BUSINESS LETTER - Pudikova, G.N. (RUDN Journal of Language Studies, Semiotics and Semantics, 2018)
The algorithm of analysis of business letter in Russian, English and Portuguese languages on the basis of next aspects: style and genre, structure-semantic and pragmatic features, pragmatic information, genre varieties are presented in the article. A business letter as the type of text that has the special communicative structure and provided with documentary force grammatically executed and semantically completed is certained here. It is shown that pragmatic information in texts of business letter will be realized through the grammatical category of modality and pragmatic category of business politeness, that explisite in hyperbolae, formulas of politeness and indirect speech act of request. A commitment letter as the form of business correspondence is examined. A commitment letter is presented as a document, in that a sender promises or guarantees to carry out implementation of some actions in regard to an addressee, that conected with its interests. The aim of the article: to investigate the specific of analysis of business letters in Russian, English and Portuguese.